Junk Food Consumption and Symptoms of Mental Health Problems: A Meta-Analysis for Public Health Awareness - Hafizurrachman, Muhammad; Hartono, Risky Kusuma (Kesmas, 2021)
Junk food consumption increases the risk of having symptoms of mental health problems. This study aimed to conduct a meta-analysis to assess the association between junk food and symptoms of mental health problems. Six researchers, two primary researchers, and four assistant researchers, from October to December 2020 conducted a systematic literature review. The data sources were selected from Pubmed and Science Direct articles published from 2010 to 2020. Those websites were check-marked for text availability for original articles, using keywords for junk foods and mental health. This study had inclusion criteria for selecting and organizing articles using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. The full-text articles were selected for conducting a meta-analysis using R Studio Software. The 5,079 article titles were obtained, seven of which met the relevant requirements for meta-analysis. The range of respondents who experienced symptoms of mental illness was 1.38%–79.8%. There was no heterogeneity based on the Tau-square test. The correlation coefficient was 0.11 (95% CI 0.09–0.14), with no publication bias based on Egger’s Regression test (0.6023 or p-value>0.05). The frequent consumption of junk food can contribute to mental illness symptoms, even with minimal effects.